(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In animation the issue of movement is central to any discussion of its nature, irrespective of its form, style or process of creation. As an animator, Norman McLaren believed “the most important thing in film is motion, movement” (in Benghazi, 1994:117), whilst Wells describes animated films as “the artificial creation of the illusion of movement in inanimate lines and forms” (1998:10). Movement is of primary concern in this simple definition and in earlier critical analyses of animation, Sergei Eisenstein “ recognised ‘if it moves, then it’s alive’” [italics in original] (Leyda, 1988:54 quoted in Wells, 1998:14). This paper considers the concept of movement in animation films expressed in the kine sic performance of the character(s).